Looking beyond the Skin: Pathophysiology of Cardiovascular Comorbidity in Psoriasis and the Protective Role of Biologics - Isabel Andújar; Juan V. Esplugues; Patricia García-Martínez (MDPI AG, 2022)
Psoriasis is a chronic systemic inflammatory disease associated with a higher incidence of cardiovascular disease, especially in patients with moderate to severe psoriasis. It has been estimated that severe psoriasis confers a 25% increase in relative risk of cardiovascular disease, regardless of traditional risk factors. Although the underlying pathogenic mechanisms relating psoriasis to increased cardiovascular risk are not clear, atherosclerosis is emerging as a possible link between skin and vascular affection. The hypothesis that the inflammatory cascade activated in psoriasis contributes to the atherosclerotic process provides the underlying basis to suggest that an anti-inflammatory therapy that improved atherosclerosis would also reduce the risk of MACEs. In this sense, the introduction of biological drugs which specifically target cytokines implicated in the inflammatory cascade have increased the expectations of control over the cardiovascular comorbidity present in psoriasis patients, however, their role in vascular damage processes remains controversial. The aim of this paper is to review the mechanistic link between psoriasis and cardiovascular disease development, as well as analyzing which of the biological treatments could also reduce the cardiovascular risk in these patients, fueling a growing debate on the modification of the general algorithm of treatment.